Development of E-Linum Kids to Improve Numeracy Literacy Skills in Early Childhood to Elementary School - Ngaisah, Nur Cahyati; Kusuma, Wening Sekar (Universitas Islam Negeri Raden Intan Lampung, 2025)
Misconceptions of Kindergarten and Elementary School curriculum occur in several educational institutions related to children's ability to read, write and count. Basic mathematics skills have not been fully mastered because the learning media still uses traditional media such as worksheets, so it requires interesting interactive media such as E-Linum Kids. The purpose of this study was to develop and test the effectiveness of the E-Linum Kids application to improve numeracy literacy skills in early childhood in the transition to elementary school. The method applied in this study is Research and Development (R&D) with reference to the development of Brog and Gall. This study uses six development steps, namely 1) potential and problems, 2) data collection, 3) E-Linum Kids product design, 4) Validation of media expert designs and materials related to E-Linum Kids products, 5) Revision of E-Linum Kids design and 6) Product trials. The subjects of the study were 40 elementary school. Data were collected through observation, tests, questionnaires, and documentation.The analysis techniques in this study consist of qualitative and quantitative analysis. Qualitative analysis describes expert validation data, responses from educators and students. While quantitative analysis uses questionnaires and tests from pretest and posttest. The results of the study indicate that the game-based application E-Linum Kids successfully developed and effective for students elementary school. This is proven by the validation of media experts and material experts who obtained a very feasible category, while the response of educators to students also obtained a very feasible category. Based on the posttest results, the category has developed according to expectations in numeracy literacy skills after using the E-Linum Kids application.